Sosialisasi Peningkatan SDM Perangkat Desa Melalui Program Pendidikan S1 di Kecamatan Tano Tombangan - Siregar, Evitamala; Priyono, Cipto Duwi; Sihombing, Edi Epron; Nursalamah; Siregar, Rini Kesuma; Meidipa, Lisa Fitri (Yayasan Kajian Riset Dan Pengembangan Radisi, 2024)
The aim of this team is for village officials to have skills and knowledge in managing villages through Strata 1 Education. The research location is in Tano Tombangan District. The method used by the PKM team is a method that is generally often used during outreach, namely the lecture method. Because the lecture method is most appropriate to use to socialize the importance of increasing human resources in Malulu village officials at the tertiary level. As a result of the socialization carried out, it was discovered that there were several village officials who were interested in continuing their undergraduate education, there were around 17 village officials who wanted to continue to higher education, both the village head and his staff. And the conclusions obtained are that there are several duties and authorities of the village head related to village administration, development, training and empowerment. If it is related to the graduation rate of village heads who are only junior high school or high school graduates, then this is not in accordance with the village head's duties and authority because in carrying out these duties the village head should receive education through lectures so that the village head has knowledge about how to manage the village.